2005
DOI: 10.1016/j.neuroscience.2004.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial expression of ceramide in Alzheimer's disease brains: A role during neuronal apoptosis

Abstract: Accumulating evidences indicate that ceramide is closely involved in apoptotic cell death in neurodegenerative disorders and aging. We examined ceramide levels in the cerebrospinal fluid (CSF) or brain tissues from patients with neurodegenerative disorders and the mechanism of how intra- and extracellular ceramide was regulated during neuronal apoptosis. We screened the ceramide levels in the CSF of patients with neurodegenerative disorders, and found that ceramide was significantly increased in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
143
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 59 publications
10
143
1
1
Order By: Relevance
“…Two forms of Aβ are generally used for in vitro studies, fibrillar and oligomer. Several studies suggest that fibrillar Aβ induces primary neuron apoptosis via the activation of NSM (Ayasolla et al, 2004;Chen et al, 2006;Jana and Pahan, 2004;Lee et al, 2004;Satoi et al, 2005;Zeng et al, 2005). However, our data using postmortem AD brain revealed that ASM, not NSM, activity was elevated.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Two forms of Aβ are generally used for in vitro studies, fibrillar and oligomer. Several studies suggest that fibrillar Aβ induces primary neuron apoptosis via the activation of NSM (Ayasolla et al, 2004;Chen et al, 2006;Jana and Pahan, 2004;Lee et al, 2004;Satoi et al, 2005;Zeng et al, 2005). However, our data using postmortem AD brain revealed that ASM, not NSM, activity was elevated.…”
Section: Discussioncontrasting
confidence: 81%
“…In vitro, Aβ has been shown to induce apoptosis via the sphingomyelin/ceramide pathway in various brain cells, including human and rat primary neurons (Jana and Pahan, 2004;Ju et al, 2005;Malaplate-Armand et al, 2006), rat oligodendrocytes (Cheng et al, 2003;Lee et al, 2004;Malaplate-Armand et al, 2006;Zeng et al, 2005), rat astrocytes and glial cells (Ayasolla et al, 2004), and murine neuroblastoma cells (Satoi et al, 2005). Calcium-dependent phospholipase A (cPLA) (Malaplate-Armand et al, 2006), inducible nitric oxide synthase (iNOS) (Ayasolla et al, 2004;Zeng et al, 2005), the p75 neurotrophin receptor (p75NTR) (Costantini et al, 2005), and NADPH oxidase (Jana and Pahan, 2004) have each been shown to be involved in the Aβ-related activation of the sphingomyelin/ceramide pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conflicting results could be due to the stage of the disease process studied. One CSF study reported higher ceramide levels in moderate versus mild or severe AD [28], while another examining brain tissue reported that the gene expression patterns of enzymes participating in the sphingolipid metabolism pathway varied by AD severity [18]. Similarly, we found serum SM and ceramides varied by time to onset of memory impairment, such that levels were higher pre-symptomatically but lower at the time of impairment.…”
Section: Discussionsupporting
confidence: 58%
“…Limited clinical research has examined the role of SM and ceramides in AD pathogenesis. Post-mortem studies and the one CSF study suggest AD cases have higher levels of SM and/or ceramides [7,13,25,26,28]. Importantly, levels also vary by disease severity [7,13,28], suggesting the possible use of these lipids as biomarkers of AD progression.…”
Section: Introductionmentioning
confidence: 98%